Characterization of atypical Aeromononas salmonicida infection in Arctic charr (Salvelinus alpinus) and European grayling (Thymallus thymallus) - Pylkkö, Päivi; Pohjanvirta, Tarja; Madetoja, Jari; Pelkonen, Sinikka (de, 2005)
v 2005 ok